Twin Peaks: The Emergence of Bimodal Fertility Profiles in Latin America - Everton E. C. Lima; KryRYštof Zeman; Mathias Nathan; Ruben Castro; Tomáéš Sobotka (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2017)
In contrast to most other low-fertility regions, the fall in period fertility to subreplacement level in Latin America was not accompanied by a sharp decline in fertility rates at young reproductive ages. Reconstructing period fertility rates by age, birth order and level of education, we investigate changes in the age pattern of childbearing in four Latin American countries that experienced a decline in period total fertility rates below the replacement level in the early 2000s - Brazil, Chile, Costa Rica and Uruguay. Our analysis shows that all the four countries display a combination of continuing high rates of childbearing at younger ages with a parallel increase in first birth rates at later reproductive ages. This pattern is also manifested by the emergence of bimodal schedules of first birth rates by age, especially in Chile and Uruguay. We show that this reproductive polarization is more pronounced than the bimodal profiles identified earlier for selected countries of Europe and the United States. We suggest that Latin American low fertility pattern is linked to a high level of income inequality and wide social status differences in the region that go hand in hand with a high rate of unplanned early pregnancies and births, especially among women with lower education.
Keywords: 300; First birth; fertility timing; family formation; age schedule of childbearing; Latin America